The effect of relationships with government-owned banks on cash flow constraints: Evidence from India - Srinivasan, Anand; Thampy, Ashok (Journal of Corporate Finance, 2017)
We examine the effect of maintaining exclusive relationships with Government Owned Banks (GOBs) on real investment by publicly traded companies in India. Firms that maintain such exclusive relationships have an investment cash flow sensitivity that is almost 30% lower relative to other firms. GOB relationships also increase sensitivity of investment to Tobin's Q. Exclusive relationships with private banks increase cash flow sensitivity while exclusive relationships with foreign banks have no impact. The lower investment cash flow sensitivity by firms with exclusive GOB relationships is not the result of cherry picking of less constrained firms by GOBs. Rather, firms with exclusive GOB relationships are in worse financial condition relative to other firms – thus, GOBs appear to be doing reverse of cherry picking. Surprisingly, the results are driven by the large firms which benefit from GOB relationship and not the smaller firms which are the intended beneficiaries of government directed credit programs.